A triazole linkage that mimics the DNA phosphodiester group in living systems. Issue 4 (16th July 2015) - El-Sagheer, Afaf H.; Brown, Tom
Abstract: We describe the development of a chemical process based on the CuAAC reaction (click chemistry) to ligate DNA strands and produce an unnatural triazole backbone linkage. The chemical reaction is templated by a complementary DNA splint which accelerates the reaction and provides the required specificity. The resultant 1, 4-triazole linkage is read through by DNA and RNA polymerases and is biocompatible in bacterial and human cells. This work has implications for the synthesis of chemically modified genes and other large modified DNA and RNA constructs.